PERANCANGAN RANGKA GOKAR LISTRIK - Hafidz Ammar Haryono Putro; Stenly Tangkuman; Michael Rembet (JURNAL POROS TEKNIK MESIN UNSRAT, 2015)
ABSTRACT The purpose of this research is to get a design of a frame for an electric gokart. The frame serve as a foundation for putting the vehicle body, engine, steering systems, and other components. This research was conducted using structural statics calculation and mechanics of material strength that can determine the load on the frame and the maximum load that can be sustained by the frame. In this design of electric gokart frame using a ST 37 pipe tube material which has a yield strength at allowable strength at 117,5 MPa. The tube has a outer radius 12,7 mm and inner radius 12,5 mm. The results of this design is an engineering drawing of an electric gokart frame. Keyword: Design, Frame, Yield strength, Allowable Strength.